Health-Related Physical Fitness for Children With Cerebral Palsy. (August 2014) - Maltais, Désirée B.; Wiart, Lesley; Fowler, Eileen; Verschuren, Olaf; Damiano, Diane L.
Low levels of physical activity are a global health concern for all children. Children with cerebral palsy have even lower physical activity levels than their typically developing peers. Low levels of physical activity, and thus an increased risk for related chronic diseases, are associated with deficits in health-related physical fitness. Recent research has provided therapists with the resources to effectively perform physical fitness testing and physical activity training in clinical settings with children who have cerebral palsy, although most testing and training data to date pertains to those who walk. Nevertheless, on the basis of the present evidence, all children with cerebral palsy should engage, to the extent they are able, in aerobic, anaerobic, and muscle-strengthening activities. Future research is required to determine the best ways to evaluate health-related physical fitness in nonambulatory children with cerebral palsy and foster long-term changes in physical activity behavior in all children with this condition.